Interactions within climate policyscapes: a network analysis of the electricity generation space in the United Kingdom, 1956–2022 - Zambianchi, Valeria; Biedenkopf, Katja (Frontiers in Climate, 2024)
The systems of policies impacting climate change mitigation are complex. Yet, to date, we have limited conceptual and empirical knowledge on the dynamics within these. We address this gap by employing a systems lens to untangle the interactions between the policies affecting climate change mitigation in the electricity generation space. We conceptualise climate policyscapesfor electricity generation as systems populated with policies whose means impact decarbonisation in the electricity generation space. The impacts under analysis include both support and obstruction of climate change mitigation. We analyse the evolution of the UK climate policyscape from 1956 to 2022. Methodologically, we combine qualitative content analysis and network analysis. We populate the policyscapes with pieces of legislation in the electricity generation space and employ qualitative content analysis to identify the policy means affecting climate change mitigation. Our network analysis of the 2022 climate policyscape reveals that policies hindering climate mitigation remain largely present, which renders the climate policyscape incoherent. We show that policies supporting mitigation are more likely to behave as a group than policies hindering climate mitigation. Climate policies tend to be adopted as packages, whilst fossil policies remain a steady process throughout the history of the UK climate policyscape.